Self-adaptive root-like capillary diffusion channels enabled by TaN/Zr3N4 nanomultilayered architecture: Achieving superior corrosion resistance. (January 2023) - Qi, J.L.; Wang, L.P.; Hao, J.; Zhang, Y.; He, X.J.; Pang, H.P.; Zhang, K.; Wen, M.
Graphical abstract: Highlights: N -rich Zr3 N4 nanolayers were utilized to construct TaN/Zr3 N4 nanomultilayered architecture. The superior mechanical properties enabled by local c-TaN/c-Zr3 N4 coherent growth. The biomimetic root-like capillary diffusion channels were endowed by the ultra-fine TaO2 @ZrO2 core-shell structure. The novel channels led corrosion front terminate in same Zr3 N4 nanolayer with several-nm scales accuracy. Abstract: The combined merits of high hardness and superior chemical inertness enable transition metal nitrides (TMNs) to be extensively coated onto the metal surfaces for avoiding erosion and corrosion attacks. However, the relatively large-size through-type diffusion channels commonly appear in the corroded layers as TMNs coatings subjected to corrosive environments. These channels can serve as short-circuit-diffusion paths for corrosive ions and worsen the corrosion-resistance ability, eventually, yielding unpredictable failure due to the heterogeneous growth of corrosion products. Obviously, comparing with the large-size through-type diffusion channels, the biomimetic multi-forked root-like capillary channels can significantly extend the diffusion distance and retard the transportation of corrosive ions by continuously deflecting and refining the diffusion paths. Herein, the nano-laminated TaN/Zr3 N4 architecture, consisting of alternating 10 nm-thickness c-TaN nanolayers and 2 nm-thickness N -rich o-Zr3 N4 nanolayers, has been fabricated by magnetron sputtering technology; it exhibits the characteristic of c-TaN/c-Zr3 N4 local coherent growth. Such TaN/Zr3 N4 nanomultilayered structure contributes to the self-adaptive assembly of TaO2 @ZrO2 core–shell nanostructure in the corroded layer, thereby yielding appearance of uniformly root-like capillary diffusion channels instead of the typical through-type diffusion channels in the constitute monolayers; finally, it achieves superior corrosion-resistance with homogeneously general corrosion rate and avoids the uncontrollable failures.